Allele Mining in Barley Genetic Resources Reveals Genes of Race-Non-Specific Powdery Mildew Resistance - Spies, Annika; Korzun, Viktor; Bayles, Rosemary; Rajaraman, Jeyaraman; Himmelbach, Axel; Hedley, Pete; Schweizer, Patrick (Frontiers in Plant Science, 2012)
Race-nonspecific, or quantitative, pathogen resistance is of high importance to plant breeders due to its expected durability. However, it is usually controlled by multiple quantitative trait loci (QTL) and therefore difficult to handle in practice. Knowing the genes that underlie race-nonspecific resistance would allow its exploitation in a more targeted manner. Here, we performed an association-genetic study in a customized worlwide collection of spring barley accessions for candidate genes of race-nonspecific resistance to the powdery mildew fungus Blumeria graminis f.sp. hordei (Bgh) and combined data with results from QTL-mapping- as well as functional-genomics approaches. This led to the idenfication of 11 associated genes with converging evidence for an important role in race-nonspecific resistance in the presence of the Mlo-gene for basal susceptibility. Outstanding in this respect was the gene encoding the transcription factor WRKY2. The results suggest that unlocking plant genetic resources and integrating functional-genomic with genetic approaches accelerates the discovery of genes underlying race-nonspecific resistance in barley and other crop plants.